INVENTARISASI SERANGGA HAMA PADA KOPRA DI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - CATHERINE.E. GABRIEL; J. MANUEKE; E. R.M. MERAY; T. OGIE (Universitas Sam Ratulangi, 2020)
ABSTRACTThis study aims to determine the pest insects that attack copra commodities and determine thepopulation density of each type or species of pest insects that attack copra in Tobelo District,North Halmahera Regency. The research method used was a survey method. The survey wasconducted at a copra warehouse in Rawajaya Village, Gosoma Village, and Wosia VillageTobelo District, North Halmahera Regency. Sampling uses the method